BENTUK DAN ARTI SENI HIAS PADA MASJID BESAR KAUMAN YOGYAKARTA - Muhammad Chawari (Berkala Arkeologi, 2000)
Generally the Javanese convey their messages often indirectly. This means that messages or things related to aesthetics are conveyed through or using certain signs or images. The use of these signs is closely related to the teachings of the Islamic religion, considering that the image or decorative art to be presented is inside the holy building, namely the mosque. Likewise, the existence of refractive art found in the Great Mosque of Kauman Yogyakarta.